ASSESSING APTITUDES and YOUSCIENCE: Enhancing Career Development for Learners of All Ages. - Feller, Rich; Hardin, Philip; Cunningham, Toby; Whichard, Judy; Long, Jenn (Career Planning & Adult Development Journal)
The article discusses the use of assessments to encourage individual success and life design. Topics covered include measuring individual differences via general intelligence assessments or standardized achievement tests, the significant differences in aptitude requirements across jobs, and the re-integration of aptitudes as an essential part of the holistic picture of self and talent development.